Stosunki amerykańsko-indyjskie w XXI wieku. Implikacje geopolityczne - Jakimowicz, Robert (Forms of Power in Contemporary World – Case Studies, 2023)
In this article, the author presents and analyzes U.S.- India relations in the twenty-first century, which are fundamentally different from previous ones during the Cold War and before the collapse of the Soviet Union. The introduction sets out the premises that prevented good relations between the US and India during the Cold War. Then, in three parts, the dynamics of American-Indian relations are presented and analyzed. On the other hand, the conclusions summarise the most important factors that have become the basis of the current relations between the two countries.